ELT IN INDONESIAN CONTEXT: Issues and Challenges - Rahmat Yusny (Englisia: Journal of Language, Education, and Humanities, 2013)
This paper is aimed to render an analysis on how the impression of linguistic imperialism of English in the era of globalization would affect Language Teaching of English in Indonesian context. English is known to globally spread very rapidly. Starting from the two major diasporas in 16th and 18th century, now, English is accepted in even more countries through the initiatives which is claimed as a practice of Linguistics Imperialism. Indonesia, unlike other neighboring countries such as Singapore, Malaysia, and the Phillipines, has a very little exposure on English due to never become regulated under the British colonial. Hence, English has never been widely spoken in the Indonesian society. But in contrast, English is taught in Indonesian schools as a compulsory subject in grade 7 of secondary school to University levels and considered very important compared to other subjects in Indonesian education system. This is proven by the fact that English is tested the Indonesian national examination (Minister of National Education, 2007). This paper discusses about both the historic view and present-day view of ELT as a form of Linguisitics Imperialism to be noted and anticipated in the practice of ELT in Indonesia in order to plan for a more benefitting reason. Hopefully, by being aware of these issues and accusations, ELT in Indonesia will advance better in the future.